Poverty dynamics analysis: a case of agricultural households in Indonesia - Fitrah Amalia; Tri Haryanto; Wahyu Wisnu Wardana (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2026)
The first goal of the Sustainable Development Goals (SDGs) is to eradicate poverty by 2030. In Indonesia, achieving this goal requires particular attention to the agricultural sector, where a large share of the poor population is concentrated. This study examines poverty dynamics among agricultural households in Indonesia using data from the Indonesian Family Life Survey (IFLS) for 2007 and 2014, applying a spell approach. The findings indicate that temporary (transient) poverty accounts for 74.55% of total poverty, while chronic poverty constitutes 25.45%. Furthermore, the results from the ordered logit model reveal that dynamic poverty is significantly influenced by the household head’s age and education level, household size, gender, access to electricity and financial credit, residential location (within or outside Java), as well as changes in household size, education level, access to credit, and land ownership.